Prediksi Terhadap Emisi Karbon Dari Kegiatan Transportasi Di Wilayah Pengembangan V (WP V) Kota Pekanbaru - Harimurti, M. Arief; Reza, Muhammad; Sasmita, Aryo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Pekanbaru City as the capital city of Riau Province has increase in population especially in development area V (WP V). It was followed by an increase in the number of vehicles as a transportation and affect the amount of CO2 emissions generated from each vehicles. Green Open Space (RTH) is one of solution in order to handling the increasing of emissions because by absorb CO2 gas emissions. This research was conducted to determine the amount of motorized vehicles and the value of CO2 emissions produced each day, as well as the value of the ability of the green space absorption of CO2 emissions. The method used is recording traffic activities to calculate the amount of CO2 emissions and calculate all public green open space with a type of vegetation cover in the form of grasslands and trees that have a diameter of â‰¥ 20 cm, and the percentage of green space absorption. Research results obtained, namely the value of CO2 emissions from transportation in Pekanbaru Development Area V amounted to 595.029,20 tons of CO2 / year. While the ability to absorb CO2 by public green space in the Pekanbaru Development Area V is only 24.806,82 tons of CO2 / year. The results of the analysis show that public green open space in the Development Area V Pekanbaru in terms of absorption of CO2 emissions from transportation is still not enough with a percentage of only 3,72 %. Power absorption of green space is planned to reduce all CO2 emissions from transportation activities in Pekanbaru Development Area V, which is 869.365,529 tons of CO2 / year. Key Words : CO2 Emissions, Green Open Space, Pekanbaru Development Area V, Transpotation